Research into the efficiency of Chinese stock markets - Wang, Wenze (2019)
The proposal of an Efficient Market hypothesis is of great significance. The hypothesis explains the pricing mechanism for the market price of securities. This is highly influential to the theoretical understanding of the modern securities market. Developmental history indicates that this theoretical viewpoint has made an outstanding contribution to the development of the capital market. China’s stock market has achieved remarkable development since its establishment. Therefore, both domestic and foreign scholars have conducted empirical studies to better understand the effectiveness of China’s stock market. The results obtained by different researchers, however, are relatively contradictory. Thus, for purpose of evaluating the degree of development and effectiveness of the Chinese stock market, it is necessary to take a systematic approach. This dissertation is based on the Efficient Market Hypothesis（EMH）. It is presented in four distinct sections. The first section presents a systematic introduction to the EMH, including its definition, empirical implications and testing methods. The second part categorizes and summarizes relevant literature around the world, examining the methodology, sample data and models. The third section utilizes different methods to carry out empirical research into the weak-form efficiency and semi-strong form efficiency of Shanghai and Shenzhen stock markets. The final section considers possible reasons for the inefficiency of the Chinese stock market and provides some suggestions for the development of Chinese securities market.